Audience Emotional Expression and Communication Culture in Esports: A Netnographic Study of YouTube Live Chat in Mobile Legends Bang Bang M7 World Championship Final Indonesia vs Philippines - Mochammad Sirojul Munir Hamidi Yusuf (Indonesian Journal Publisher, 2026)
This study examines the emotional expressions and communication culture of Indonesian and Filipino audiences in the YouTube live chat during the Mobile Legends: Bang Bang M7 World Championship Grand Final held on January 25, 2026, in Jakarta. The final between Aurora Gaming PH (Philippines) and Alter Ego (Indonesia), won by Aurora PH with a 4-0 score, generated 2,601 comments analyzed in this study. Employing a qualitative approach through netnography, this research applies Martin and White's Appraisal Theory as the analytical framework for evaluative language. Findings reveal that Filipino audiences' emotional expressions moved linearly from anxiety to intense celebratory euphoria, while Indonesian audiences displayed a more complex emotional spectrum: from initial pride, disappointment, strategic criticism, and systemic frustration to sportsmanship. Both groups' communication cultures demonstrate patterns of collective identity affirmation, symbol-based national support, competitive mockery, and cross-group sportsmanship. The communal narrative of #CumaEvos emerged as a discursive resilience mechanism within the Indonesian community. Similarities between both groups include the use of high graduation force, identity assertion, aggressive communication, and sportive expressions. Key differences lie in emotional orientation, responses to defeat, language use, and temporal orientation of comments. This study contributes to digital communication studies, participatory culture, and esports research in Indonesia.